2018
DOI: 10.1016/j.beproc.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Grouping promotes risk-taking in unfamiliar settings

Abstract: Acting collectively in a group provides risk-reducing benefits. Yet individuals differ in how they take risks, with some being more willing than others to approach dangerous or unfamiliar settings. Therefore, individuals may need to adjust their behaviour when in groups, either as a result of perceiving greater safety or to coordinate collective responses, the latter of which may rely on within-group dynamics biased by group composition. In zebrafish we explored how these aspects of grouping affect risk-taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Firstly, individuals may make faster decisions when they are in groups due to a reduced perception of risk and/or greater perception of competition (Magurran & Pitcher, 1983;Grand & Dill, 1999), an effect which does not rely on information transfer between individuals. Such an effect is consistent with individuals in groups being bolder (i.e., less risk averse) and more active than solitary individuals (McDonald et al, 2016;Kareklas et al, 2018). Larger groups are also statistically more likely to contain individuals that make decisions more rapidly, for example because these individuals are less risk averse (i.e., are bolder (Ioannou & Dall, 2016)), hungrier (Balaban-Feld et al, 2019), or better informed (Ioannou et al, 2015).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Firstly, individuals may make faster decisions when they are in groups due to a reduced perception of risk and/or greater perception of competition (Magurran & Pitcher, 1983;Grand & Dill, 1999), an effect which does not rely on information transfer between individuals. Such an effect is consistent with individuals in groups being bolder (i.e., less risk averse) and more active than solitary individuals (McDonald et al, 2016;Kareklas et al, 2018). Larger groups are also statistically more likely to contain individuals that make decisions more rapidly, for example because these individuals are less risk averse (i.e., are bolder (Ioannou & Dall, 2016)), hungrier (Balaban-Feld et al, 2019), or better informed (Ioannou et al, 2015).…”
Section: Introductionsupporting
confidence: 57%
“…Our experiment shows that the speed of decision making is affected by group size in fish from low predation habitats more than in fish from high predation habitats, at least in small groups from 2 to 8 individuals. The time taken to reach the decision zone followed the expected direction that larger groups were quicker to leave the start area, and hence were bolder and more exploratory than smaller groups (McDonald et al, 2016;Kareklas et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…Environmental factors have also been studied in zebrafish by modifying environmental conditions (e.g., by stressing the fish before testing or treating them developmentally with alcohol or nicotine). Several recent studies have addressed the impact of environmental enrichment or impoverish on zebrafish, involving complex cognitive (Collymore, Tolwani, & Rasmussen, ; DePasquale, Neuberger, Hirrlinger, & Braithwaite, ; Manuel et al, ; Spence, Magurran, & Smith, ) and/or social (Kareklas, Elwood, & Holland, ; Seguret, Collignon, & Halloy, ; Wafer et al, ) contexts. For instance, environmental enrichment exerts beneficial effects on brain and behavior in both wild‐type and genetically modified zebrafish (Collymore et al, ; Manuel et al, ; Wafer et al, ).…”
Section: Zebrafish As a Novel Model Organism For Neuroscience Researchmentioning
confidence: 99%
“…For example, the behaviour of zebrafish housed in groups has been shown to return to normal levels after handling more quickly than in paired or isolated fish [ 54 ], suggesting that the presence of a group promoted faster recovery from stress. In another study, group-housed fish were bolder than isolated fish in a novel object test, which may suggest that the presence of other individuals led to greater feelings of safety, which in turn could indicate a better welfare state [ 62 ]. However, some studies have shown that isolated fish mount a smaller response to a stressor than group-housed fish [ 60 , 63 ], while another found that isolated fish had smaller cortisol responses than group-housed fish to being chased with a net, but bigger responses to predation stress [ 59 ].…”
Section: Defining and Evaluating Environmental Enrichmentmentioning
confidence: 99%